Pengaruh Disiplin Kerja Dan Komunikasi Terhadap Kinerja Karyawan: Studi pada CV Mendong K Craft Tasikmalaya - Nanda Nurpriyana; Ferey Herman; Apri Budianto (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
The problems faced in this study include (1) How does work discipline affect employee performance at CV Mendong K Craft Tasikmalaya, (2) How does communication affect employee performance at CV Mendong K Craft Tasikmalaya, (3) How do discipline and communication affect employee performance at CV Mendong K Craft Tasikmalaya.? This study aims to study, find out, and analyze (1) Work discipline of CV Mendong K Craft Tasikmalaya employees. (2) Communication of CV Mendong K Craft Tasikmalaya employees. (3) Performance of CV Mendong K Craft Tasikmalaya employees. (4) Effect of Discipline and Communication on the Performance of CV Mendong K Craft Tasikmalaya. The method used in this study is an explanatory survey, while the technical data analysis, namely validity test, reliability test, descriptive statistics, Inductive Statistical Analysis (Inferential) with Multiple Regression. The results of the study inform that (1) Work discipline has a positive effect on employee performance at CV. Mendong K Craft Tasikmalaya. This means that if work discipline is improved, then employee performance at CV. Mendong K Craft Tasikmalaya will also improve. (2) Communication has a positive effect on employee performance at CV. Mendong K Craft Tasikmalaya. This means that if communication is improved, then employee performance at CV. Mendong K Craft Tasikmalaya will also improve. (3) Work discipline and communication have a positive effect on employee performance at CV. Mendong K Craft Tasikmalaya. This means that if work discipline and communication are improved, then employee performance at CV. Mendong K Craft Tasikmalaya will also improve.